Epigenetic Heterogeneity in Friedreich Ataxia Underlies Variable FXN Reactivation - Rodden, Layne N.; Gilliam, Kaitlyn M.; Lam, Christina; Lynch, David R.; Bidichandani, Sanjay I. (Frontiers in Neuroscience, 2021)
Friedreich ataxia (FRDA) is typically caused by homozygosity for an expanded GAA triplet-repeat in intron 1 of the FXN gene. The expanded repeat induces repressive histone changes and DNA hypermethylation, which result in epigenetic silencing and FXN transcriptional deficiency. A class I histone deacetylase inhibitor (HDACi-109) reactivates the silenced FXN gene, although with considerable inter-individual variability, which remains etiologically unexplained. Because HDAC inhibitors work by reversing epigenetic silencing, we reasoned that epigenetic heterogeneity among patients may help to explain this inter-individual variability. As a surrogate measure for epigenetic heterogeneity, a highly quantitative measurement of DNA hypermethylation via bisulfite deep sequencing, with single molecule resolution, was used to assess the prevalence of unmethylated, partially methylated, and fully methylated somatic FXN molecules in PBMCs from a prospective cohort of 50 FRDA patients. Treatment of the same PBMCs from this cohort with HDACi-109 significantly increased FXN transcript to levels seen in asymptomatic heterozygous carriers, albeit with the expected inter-individual variability. Response to HDACi-109 correlated significantly with the prevalence of unmethylated and partially methylated FXN molecules, supporting the model that FXN reactivation involves a proportion of genes that are amenable to correction in non-dividing somatic cells, and that heavily methylated FXN molecules are relatively resistant to reactivation. FXN reactivation is a promising therapeutic strategy in FRDA, and inter-individual variability is explained, at least in part, by somatic epigenetic heterogeneity.